Correlation of Seed and Seedling Characters with Yield of Sunflower (Helianthus annuus L.) Hybrids - S. S. Nichal; R. G. Chawhan; S. D. Tayade; R. D. Ratnaparkhi (International Journal of Economic Plants)
The experiment was conducted at Oilseeds Research Unit and at Seed Testing Research Unit, Dr. PDKV, Akola, Maharashtra, India during kharif 2012, to study the correlation of seed and seedling characters with yield of sunflower hybrids. The experiment consisted of eight sunflower hybrids and was laid out in randomized block design with three replications. The character association revealed that the seed characters viz., kernel to hull ratio (0.986), % seed kernel (0.984), volume weight (0.783) and hundred seed weight (0.741) showed highly significant positive correlation with yield plant-1, indicating that yield of sunflower hybrids could be increase by increase in these seed characters. The seed characters like % seed hull (-0.949) and electrical conductivity of seed leachate (-0.407) recorded significant negative correlation with yield plant-1, indicating, decrease in these characters will results in increase in yield. All the seedling characters studied viz., % germination (0.976), root length (0.986), shoot length (0.729), seedling vigour index (0.966) and seedling dry weight (0.841) shown highly significant positive correlation with seed yield plant-1 indicating the vital role of these characters towards corresponding gain in yield of sunflower hybrids. The sunflower hybrids shown high value of desirable seed and seedling characters also yielded higher, this may be due to high germination and early vigour of these hybrids. Thus, more emphasis should be given on seed and seedling characters, as an early indicator of yield performance and seed and seedling characters may be used as selection criteria for identification of high yielding sunflower hybrid.